Educação e tecnologia: a evolução de tecnologias usadas na educação e no curso de pedagogia do campus de Tocantinópolis, nos seus 30 anos. - Silva, Marcelo Henrique Militão da (Universidade Federal do Tocantins, 2021)
Technology influences the way society is organized and generates consequences in different social segments, such as health, education, economics, among others. Every day new technologies emerge, such as cell phones, computers, applications, etc., featuring a constant evolutionary process that naturally introduces itself in the life of man, becoming part of and interfering in his experiences. Considering the educational technologies as important instruments for the promotion of classes, this work sought to understand the evolution and use of educational technological resources of the last thirty years, a time space concomitant with the Pedagogy course at the Campus of the Federal University of Tocantins in Tocantinópolis. For this, four methodological research bases were used to collect the data presented here, characterized as bibliographic research, based on studies by authors such as: Bauman (2001), Jenkins (2015), Moran (2006), Cardoso (2009), Lopes, Moura and Menezes (2019), Alves (2020), among others; documentary, in the collection of the Education Memory Center (CEMED); survey in the Campus Heritage Sector; and field research , through the questionnaire applied to teachers about the use of educational technologies. The methods used for data analysis were hypothetical-deductive, deductive, qualitative and quantitative. The results showed that the evolution of educational technological resources constitutes a constant movement in which the teacher needs to be able to deal with them; it needs to have at its disposal supports that allow it to adapt to new emerging technological scenarios to conduct teaching